2022
DOI: 10.3389/fsurg.2022.941672
|View full text |Cite
|
Sign up to set email alerts
|

High Body Mass Index Is Associated with an Increased Risk of the Onset and Severity of Ossification of Spinal Ligaments

Abstract: BackgroundOssification of the posterior longitudinal ligament (OPLL) and that of ligamentum flavum (OLF) are the main types of the ossification of spinal ligaments (OSL) that cause the thoracic myelopathy. Although several studies have investigated the relationship of body mass index (BMI) with the onset or severity of OSL, it remains unverified due to the contradictory results of existing evidence. A systematic review and meta-analysis were performed in this work to determine the relationship of BMI with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
0
3
1
Order By: Relevance
“…These findings contrast with the results of previous studies that have found associations between BMI and foot position (Molina-García et al, 2023;Escalona-Marfil et al, 2022;Bann et al, 2022). Other study showed that subjects with higher BMI were at higher risk of ossification of the posterior longitudinal ligament and the yellow ligament of the spine, which may affect foot position (Zhao et al, 2022). In our study, we did not record variables relating to these spinal ligaments.…”
Section: Discussioncontrasting
confidence: 99%
“…These findings contrast with the results of previous studies that have found associations between BMI and foot position (Molina-García et al, 2023;Escalona-Marfil et al, 2022;Bann et al, 2022). Other study showed that subjects with higher BMI were at higher risk of ossification of the posterior longitudinal ligament and the yellow ligament of the spine, which may affect foot position (Zhao et al, 2022). In our study, we did not record variables relating to these spinal ligaments.…”
Section: Discussioncontrasting
confidence: 99%
“…Several studies have reported the impact of obesity and diabetes on cervical OPLL. [ 3 4 14 15 16 ] A recent meta-analysis noted that patients with spinal ligament ossification had significantly higher BMI, and that patients with higher BMI had significantly higher ligament ossification indices and more severe disease presentation compared to those with lower BMI. [ 14 ] Kobashi et al .…”
Section: Discussionmentioning
confidence: 99%
“…[ 3 4 14 15 16 ] A recent meta-analysis noted that patients with spinal ligament ossification had significantly higher BMI, and that patients with higher BMI had significantly higher ligament ossification indices and more severe disease presentation compared to those with lower BMI. [ 14 ] Kobashi et al . noted that a history of diabetes mellitus and maximum BMI >25 kg/m 2 were independent risk factors for the development of OPLL.…”
Section: Discussionmentioning
confidence: 99%
“… 10 , 20 In our previous study, we discovered that high body mass index might contribute to the onset and severity of the OLF. 21 , 22 Therefore, accumulating evidence showed that metabolic disorder might play a vital role in the pathogenesis of OLF. However, the value of metabolic disorder in OLF has not obtained adequate attention, and underlying mechanism remains unclear to date.…”
Section: Introductionmentioning
confidence: 99%